2006
DOI: 10.1253/circj.70.141
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Folic Acid and Magnesium on the Production of Homocysteine-Induced Extracellular Matrix Metalloproteinase-2 in Cultured Rat Vascular Smooth Muscle Cells

Abstract: igration of vascular smooth muscle cells (VSMCs) into the vascular intima and their subsequent proliferation and remodeling of the extracellular matrix are important events in the pathogenesis of atherosclerosis. These events are regulated by various cytokines and growth factors secreted by platelets and vascular cells. 1 Zempo et al reported that the processes of migration and proliferation of VSMCs that contribute to the morphogenesis of atherosclerotic plaque require extracellular matrix remodeling induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
2
12
0
2
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][12][13][14] Many issues regarding the mechanism of action of homocysteine in the pathogenesis of arteriosclerosis and thrombotic diseases remain unclear. However, possible causes include vascular endothelial dysfunction, [17][18][19][20][21][22] smooth muscle cell growth, [23][24][25] and an increase in blood clotting activity in vascular walls. 26,27) Elevated homocysteine levels may promote heart failure through 4 potential mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14] Many issues regarding the mechanism of action of homocysteine in the pathogenesis of arteriosclerosis and thrombotic diseases remain unclear. However, possible causes include vascular endothelial dysfunction, [17][18][19][20][21][22] smooth muscle cell growth, [23][24][25] and an increase in blood clotting activity in vascular walls. 26,27) Elevated homocysteine levels may promote heart failure through 4 potential mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported increased placental levels of MMP1 (collagenase) and MMP9 (gelatinase) in women delivering preterm (Sundrani et al 2012). The activity of MMPs is reported to be regulated by homocysteine, oxidative stress, and long-chain polyunsaturated fatty acids (LCPUFA; Guo et al 2006, Kundu et al 2009, Solakivi et al 2009, Zainal et al 2009, Zeydanli & Turan 2009, Ke et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…In another frontier study, the researchers hypothesized that Mg ion released from corroded Mg screws blocked MMP-13 expression, inhibited the degradation of collagens via tyrosine kinase inhibitors through a highlighted signaling pathway41. In previous researches, it was demonstrated that extracellular Mg reduced MMPs in a dose-dependent manner in cultured rat vascular smooth muscle cells as well as rat cardiac fibroblasts potentially via two tyrosine kinase inhibitors, genistein and herbimycin A4445. According to the hypothesis, it could be inferred that magnesium may have indirect effect on the inhibition of MMPs and suppressed the influence of magnesium on the expression of IL-6 and MMP-1 in vivo 46.…”
Section: Discussionmentioning
confidence: 99%